VD_FINDINFO Décision / 2015 / 513 vom 8. Juli 2015 - VD Tribunal cantonal (2015)
DÉTENTION PROVISOIRE, PROLONGATION, PROPORTIONNALITÉ, PRINCIPE DE LA CÉLÉRITÉ, SOUPÇON | 221 al. 1 let. c CPP (CH), 222 CPP (CH)